James Sullivan Clarkson papers - Clarkson, James Sullivan, 1842-1918.
Correspondence, speeches, articles, newspaper clippings, and printed matter, relating chiefly to Clarkson's connection with the Iowa Republican State committee, particularly his activities as delegate to the Republican national conventions (1876-1896), member of the Republican National Committee (1880-1896), and president of the Republican League of the U.S. (1891-1893); his position as editor of the newspaper, the Iowa State Register; and to his railway and other commercial interests. Includes papers relating to his service as First Assistant Postmaster General under Benjamin Harrison and surveyor of customs for the Port of New York. Correspondents include William B. Allison, Grenville M. Dodge, Jonathan P. Dolliver, Samuel Fessenden, Joseph B. Foraker, Leigh S.J. Hunt, William E. Mason, Thomas C. Platt, James F. Wilson, and George G. Wright.
In part, transcripts.
Politician, editor, and businessman.
Collection material in English.
Keywords: Allison, William B. -- 1829-1908 -- Correspondence; Dodge, Grenville Mellen, -- 1831-1916 -- Correspondence; Dolliver, Jonathan P. -- 1858-1910 -- Correspondence; Fessenden, Samuel, -- 1847-1908 -- Correspondence; Foraker, Joseph Benson, -- 1846-1917 -- Correspondence; Hunt, Leigh S. J., -- 1855-1933 -- Correspondence; Mason, William E. -- 1850-1921 -- Correspondence; Platt, Thomas Collier, -- 1833-1910 -- Correspondence; Wilson, James F. -- 1828-1895 -- Correspondence; Wright, George G. -- 1820-1896 -- Correspondence; United States. -- Post Office Department; Republican League of the U.S.; Republican Party (Iowa); U.S. Customs Service; Iowa state register; American newspapers -- Iowa -- Des Moines; Ports of entry -- New York (State) -- New York; Railroads; Iowa -- Politics and government; Businessmen; Editors; Politicians